THE USE OF ADDRESS TERMS IN FANTASTIC BEASTS AND WHERE TO FIND THEM MOVIE - Amelia, Yustika; Ekawati, Rosyida (Fakultas Ilmu Budaya, Universitas Mulawarman, 2021)
The study aims at analyzing the types of address terms used by all the characters in Fantastic Beasts And Where To Find Them movie and revealing the factors that influence the use of address terms. Both employ the theory proposed by Wardhaugh (2006). Further, this study applies to qualitative design. The result of the study can be concluded as follows. The types of address terms used in the movie are first name, title plus last name, title alone, last name, pet name, and kinship terms. The use of address terms first name was commonly used to show intimacy between the speakers. There are various factors influencing the use of address terms. They are particular occasion, social status, gender, age, family relationship, occupational hierarchy, transactional status (i.e., service encounter, or doctor-patient relationship), race, and degree of intimacy. The social status or rank of others apparently the common factor influencing the use of address terms. It is because the characters are not familiar with each other even though they know each other. Some characters also show the clear differences between the superior and the inferior. Then, the circumstances and the social background of the characters determine the use of appropriate address terms.